Pattern of heart failure in Abuja, Nigeria: an echocardiographic (2009)
Aim: Despite heart failure having been identified in subjects in sub-Saharan Africa over the last 60 years, there is still a dearth of data, especially echocardiographic data on heart failure. We therefore set out to analyse the clinical and echocardiographic features of all consecutive subjects presenting with heart failure in a tertiary institution in Nigeria. Methods: Three hundred and forty subjects with heart failure, according to the guidelines of the European Society of Cardiology, were studied. Each patient had two-dimensional guided transthoracic echocardiography. Results: The mean age of the patients was 50.60 ± 15.29 years, and 50.9% of the study population were males while 49.1% were females. The commonest cause of heart failure identified was hypertension in 61.5% of the patients; 75.5% had systolic heart failure, whereas 23.5% had heart failure with preserved ejection fraction. Conclusions: Untreated hypertension has been identified as the leading cause of heart failure in Abuja, Nigeria, which is similar to that in many other parts of sub-Saharan Africa. Coronary artery disease is a rare cause of heart failure in this population group.